Strategic retail management and brand management : trends, tactics, and examples - Berger-Grabner, Doris (De Gruyter Studium, 2021)
In this book a comprehensive coverage of major retailing topics and contemporary issues in retailing and branding is given, including many cases and practical examples. Besides introducing the topic strategic planning in retailing and fundamentals in the fields of the marketing mix in retailing, this book builds on e-tailing and digitalization. Moreover, trends and developments in consumer behavior and consumers' purchase decisions, especially in the fast moving consumer goods market, are explained. Furthermore, this book builds on the major topic strategic brand management and branding decisions in general and in particular within the retail landscape.